Diversity of Ferns (Pteridophyta) in the Montana Zone, Samiran Village, Selo District, Boyolali Regency, Central Java Province - Rahmawati, Indah; Santhyami, S (Universitas Muhammadiyah Surakarta, 2023)
Ferns (Pteridophyta) are one of the Indonesian flora groups with high diversity and wide distribution, one of which is in the montana zone, an ecosystem zone at an altitude of 1500-2400 m asl. Samiran Village is located in the District of Selo, Boyolali Regency, between two mountains, namely Mount Merapi and Mount Merbabu. This type of research was conducted at an altitude of 1600 m asl to 1800 m asl in Samiran Village, Selo District, Boyolali Regency. This study aims to determine the types of ferns and their distribution in the montane zone of Samiran Village, Selo District, Boyolali Regency. The method used is purposive sampling, a data collection technique based on points determined deliberately with a distance of 10 meters with a total of 21 points carried out in the Montane zone of Samiran village. Fern (Pteridophyta) that have been found in the montana zone of Samiran Village, are group into 2 families of 6 species consisting of Adiantum raddianum C. Presl, Notholaena copelandii c.c. Hall, Adiantum hispidulum Sw., Pityrogramma austroamericana Domin, Cyathea arborea L. Sm, Antrophyum sessilifolium (Cav.) Spr. The Diversity value (H') is 1.22, a category as relatively low. Ferns are most commonly found on soil hosts. The most abundant species were dominated by Adiantum raddianum C. Presl with 107 individuals at 14 out of 21 points. This species is one type of terrestrial fern that is also often found growing between rocks, pool walls, fences, wells, ditches, river banks other damp places. Therefore, this location is a suitable environment for the growth of Adiantum raddianum.